When Externalities Collide: Influenza and Pollution - Joshua Graff Zivin; Matthew Neidell; Nicholas Sanders; Gregor Singer (Institute of Labor Economics (IZA), 2021)
Influenza and air pollution each pose significant public health risks with large global economic consequences. The common pathways through which each harms health presents an interesting case of compounding risk via interacting externalities. Using instrumental variables based on changing wind directions, we show increased levels of contemporaneous pollution significantly increase influenza hospitalizations. We exploit random variations in the effectiveness of the influenza vaccine as an additional instrument to show vaccine protection neutralizes this relationship. This suggests seemingly disparate policy actions of pollution control and vaccination campaigns jointly provide greater returns than those implied by addressing either in isolation.
Keywords: Q53; I12; I11; 330; air pollution; influenza; hospitalizations; vaccines; externalities